2018
DOI: 10.1016/j.ipm.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

A deep network model for paraphrase detection in short text messages

Abstract: This paper is concerned with paraphrase detection. The ability to detect similar sentences written in natural language is crucial for several applications, such as text mining, text summarization, plagiarism detection, authorship authentication and question answering. Given two sentences, the objective is to detect whether they are semantically identical. An important insight from this work is that existing paraphrase systems perform well when applied on clean texts, but they do not necessarily deliver good pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 20 publications
0
67
0
2
Order By: Relevance
“…4 Ferreira et al (2018) [44] 74.08 83. 1 Agarwal et al (2018) [4] 77.7 84.5 Arora and Kansal (2019) [45] 79.0 − Our model 78.3 84.8…”
Section: Msrp Datasetmentioning
confidence: 78%
See 3 more Smart Citations
“…4 Ferreira et al (2018) [44] 74.08 83. 1 Agarwal et al (2018) [4] 77.7 84.5 Arora and Kansal (2019) [45] 79.0 − Our model 78.3 84.8…”
Section: Msrp Datasetmentioning
confidence: 78%
“…For instance, the AskUbuntu dataset [27] contains very few annotations, thus limiting the generalization performance of the model [13]. The ability to augment the data with additional sound annotations without requiring human intervention can improve the performance of deep models [4,13]. Such data augmentation has been shown to be fruitful for data analytics when only a piece of limited ordinal information about the pairwise distance between objects is provided [28,29,30].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The model computes the average of vectors of all words and n-grams in a sentence. Several studies have shown successful results produced by Sent2vec [32,33]. The model learns a context embedding v w and target embedding u w for each word w in the vocabulary, with h number of embedding dimensions.…”
Section: Sent2vecmentioning
confidence: 99%